High-Performance Liquid Chromatography (HPLC): Primary Mechanism and Popular Applications - Hammood, Raad Radi Karabat; Jasim Hammood, Ali; Abdulhusein Abdulrasool, Wad; Salam Hussein, Sabah (Al-Nahrain Journal of Science, 2024)
The concept chromatography can be used to refer to a huge variety of distinct analytical procedures. Each of these procedures utilizes a mobile phase and an immobile phase as a basic component, yet they all belong under the chromatography umbrella concept. The subsequent component separation that is carried out is based on the disparity in concentration ratio that can be detected between the two phases. This disparity acts as the basis for the subsequent component separation that is carried out. Due to the limits of current technology, there is presently no detector that is universally applicable to high-performance liquid chromatography (HPLC), it is required to choose a detector in accordance with the characteristics of the chemicals that are to be examined. The measurements of absorbance in ultraviolet and visible spectrum, known as UV-Vis, or disclosing fluorescence are the foundations of the most common types of fluorescence detectors. In HPLC the components of the apparatus consist of a carrier phase, which is typically a solvent with a buffer solution; a pump; an injector; a column; a detector; and an integrator. The column is the most important part of the system where the various components are separated from one another. Based on that, there are many various kinds of columns through which the behavior of the components to be separated by these columns is understood. Due to the fact that chromatography is such a widely used technology.